Pengaruh Inflasi Komoditas Pangan terhadap Inflasi Kota Manado (The Effect of Food Commodity Inflation on Manado City Inflation) - Jeane Monica Porwaila; Theodora M. Katiandagho; Leonardus R. Rengkung (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to determine the effect of food commodity inflation on Manado city inflation and what food commodities have a significant effect on inflation in Manado City. This research was carried out in April 2022 to May 2022. Data collection was obtained through secondary data obtained from the Central Statistics Agency. sampling using secondary data sources time series (time series). Data analysis using multiple linear regression analysis. The research results showed that inflation in Manado City was influenced by inflation of food commodities, namely inflation in the spices group. Inflation in the grains group, inflation in the vegetables group, and inflation in the fruits group did not affect the inflation in Manado City.